OsRAD17 Is Required for Meiotic Double-Strand Break Repair and Plays a Redundant Role With OsZIP4 in Synaptonemal Complex Assembly - Hu, Qing; Zhang, Chao; Xue, Zhihui; Ma, Lijun; Liu, Wei; Shen, Yi; Ma, Bojun; Cheng, Zhukuan (Frontiers in Plant Science, 2018)
The repair of SPO11-dependent double-strand breaks (DSBs) by homologous recombination ensures the correct segregation of homologous chromosomes. In yeast and human, RAD17 is involved in DNA damage checkpoint control and DSB repair. However, little is known about its function in plants. In this study, we characterized the RAD17 homolog in rice. In Osrad17 pollen mother cells (PMCs), associations between non-homologous chromosomes and chromosome fragmentation were constantly observed. These aberrant chromosome associations were dependent on the formation of programmed DSBs. OsRAD17 interacts with OsRAD1 and the meiotic phenotype of Osrad1 Osrad17 is indistinguishable from the two single mutants which have similar phenotypes, manifesting they could act in the same pathway. OsZIP4, OsMSH5 and OsMER3 are members of ZMM proteins in rice that are required for crossover formation. We found that homologous pairing and synapsis, which was roughly unaffected in Oszip4 and Osrad17 single mutant, was severely disturbed in the Oszip4 Osrad17 double mutant. Similar phenotypes were observed in the Osmsh5 Osrad17 and Osmer3 Osrad1 double mutants, suggesting the cooperation between the checkpoint proteins and ZMM proteins in assuring accurate homologous recombination in rice.